2017
DOI: 10.1159/000484060
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights into the Biological Functions of Sestrins in Health and Disease

Abstract: Sestrins (Sesns) have been identified as a family of highly conserved stress-inducible proteins that are strongly up-regulated by various stresses, including DNA damage, oxidative stress, and hypoxia. The Sesns play protective roles in most physiological and pathological conditions mainly through the regulation of oxidative stress, inflammation, autophagy, endoplasmic reticulum stress, and metabolic homeostasis. In this review, we discussed the possible regulators of Sesns expression, such as p53, forkhead box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 75 publications
1
43
0
Order By: Relevance
“…AMPK induces autophagy in response to different cellular stresses, including oxidative stress [5][6][7][8]. Although the molecular mechanism underlying how ROS modulates AMPK has not been fully established, a role for the sestrin (SESN) family has been proposed [9]. SESN2 belongs to the family of highly conserved antioxidant proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK induces autophagy in response to different cellular stresses, including oxidative stress [5][6][7][8]. Although the molecular mechanism underlying how ROS modulates AMPK has not been fully established, a role for the sestrin (SESN) family has been proposed [9]. SESN2 belongs to the family of highly conserved antioxidant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not possess intrinsic catalytic antioxidant activity, SESN2 plays an important role in suppressing ROS [10]. As a family of stress-inducible proteins, SESNs have been reported to be up-regulated and activated upon exposure to DNA damage, oxidative stress, and hypoxia [9]. There are three isoforms, including Sestrin1 (Sesn1), Sestrin2 (Sesn2), and Sestrin3 (Sesn3).…”
Section: Introductionmentioning
confidence: 99%
“…They validated this candidate in multiple animal models, demonstrating its role as a proconvulsive gene. Prior work showed that SESN3 is a regulator of the intracellular response to reactive oxygen species 15,16 and therefore is not a "classical" epilepsy gene producing an intrinsic effect on membrane excitability, such as an ion channel or neurotransmitter receptor. This work adds to the growing literature showing how deeply intertwined signaling cascades are within neural tissue, and that this interconnectedness provides novel opportunities to intervene to block seizures and comorbidities outside of traditional efforts to target channels and receptors.…”
Section: Key Pointsmentioning
confidence: 99%
“…For example, the paradoxical trend towards increase in glycogen content after IH, despite inhibition of AKT/GSK-3β, may implicate hypoxia inducible factor (HIF)-mediated induction of glycogen synthase 1 [33]. Third, in addition to JNK, changes in other stress/hypoxia-inducible pathways including Sestrins, oxidative stress, as well as microRNA profiles should be considered in interpreting the metabolic consequences of IH in liver cells [34][35][36].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%